The Effect of Democratically Determined (In)equality on Cooperative Behavior - Thomas Schlösser; Tim Steiniger; Daniel Ehlebracht; Detlef Fetchenhauer (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
We investigated the relationship between democratically determined economic inequality and cooperation in a~two-stage experimental design. Although the relationship between inequality and cooperation has been studied extensively, experimental results in this area are contradictory and find inequality to have either a~positive, negative, or no effect on cooperation. Our participants were randomly assigned to one of three societal classes (upper class, middle class, lower class) in a~simulated small-scale society, and they subsequently voted to implement a~societal system in which wealth was distributed either relatively equally or relatively unequally. We found lower levels of cooperation (measured as the invested amount in a~public-good game) among societies that previously opted for the unequal distribution, but did not observe a~general effect of a~participant's personal vote on cooperative behavior. Instead, middle-class and lower-class participants in unequal societies cooperated less than their counterparts in the equal societies, causing the observed differences on the societal level. These findings suggest that democratically induced policies that ultimately lead to greater equality of wealth are potentially able to have positive consequences on the readiness to cooperate on the production of public goods.
Keywords: 300; Inequality; Public-good game; Cooperation; Voting; Democratic decisions; Ungleichheit; Öffentliches-Gut-Spiel; Kooperation; Wahlverhalten; Demokratische Entscheidungen